Severity of Retrognathia and Glossoptosis Does Not Predict Respiratory and Feeding Disorders in Pierre Robin Sequence - Morice, Anne; Soupre, Véronique; Mitanchez, Delphine; Renault, Francis; Fauroux, Brigitte; Marlin, Sandrine; Leboulanger, Nicolas; Kadlub, Natacha; Vazquez, Marie-Paule; Picard, Arnaud; Abadie, Véronique (Frontiers in Pediatrics, 2018)
Pierre Robin sequence (PRS) may lead to life-threatening respiratory and feeding disorders. With the aim to analyze the association of the severities of retrognathia and glossoptosis with those of respiratory and feeding disorders, we retrospectively studied a series of 50 infants with retrognathia, glossoptosis, cleft palate, and airway obstruction. The patients were managed from birth to at least 6 years of age by a single pediatric team at the Armand Trousseau Hospital in Paris within a 12 years period (2000-2012). Retrognathia and glossoptosis were graded in the neonatal period according to a specific clinical examination. Ventilation assistance was required for 32/50 (64%) patients, and enteral feeding for 41/50 (82%). The grades of retrognathia and glossoptosis and the severity of respiratory disorders did not differ between patients with isolated PRS and syndromic PRS. Severe respiratory disorders were more common and long-lasting feeding (> 12 months) was more frequently required in patients with syndromic PRS compared with isolated PRS (42% vs 13%, p=0.04 and 42% vs 4%, p < 0.01 respectively). Using univariate analysis, neurological impairments and laryngomalacia were associated with severe respiratory disorders (Odds ratio (OR) 5.0, 95% CI 1.3-19.6; and OR 14.6, 95% CI 1.3-161.4; p< 0.05) as well as with long-lasting feeding (> 12 months) disorders (OR 18.6, 95% CI 3.9-89.2 and OR 20.4, 95% CI 3,4-122.8; p < 10-2). Syndromic SPR status was also associated with severe respiratory disorders (OR 4.9, 95% CI 1-32.5; p<0.05). Using multivariate analysis, only syndromic PRS status was predictive for severe respiratory disorders (adjusted OR 8, 95% CI 1.47- 44.57; p < 0.05); and only neurological impairments remained a significant risk for long lasting feeding disorders (> 12 months) (adjusted OR 21.72, 95% CI 3.4-138.63; p < 10-2). The grades of retrognathia and glossoptosis were not predictive factors for the severity of respiratory and feeding disorders. Conclusion: In children with PRS, the severity of clinical conditions may not correlate with anatomic variables but rather with laryngeal abnormalities, neurological impairement and syndromic PRS status.